Implementation Of Character Education Through BTQ Learning At SMP Negeri 5 Purwakarta - Abdurrahman Nawawi; Priest Tabroni; Nurul Fauziah (IJGIE (International Journal of Graduate of Islamic Education), 2023)
Character education today is no longer a new thing. In Purwakarta Regency, the character education policy is contained in PERBUP No. 69 of 2015. Various educational programs have been launched, including the BTQ learning program. This study aims to determine the planning, implementation, and results of character education through BTQ learning, especially at SMP Negeri 5 Purwakarta. By going through the approach qualitative-descriptive, data collection is done through observation, interviews, and documentation studies. Based on the results of the research, the characters taught through BTQ learning are the same as the characters exemplified by Rasulullah SAW. Such as religious character, honest, trustworthy, brave, responsibility, and love. BTQ learning is carried out through reading (qira'ah), writing (khat) lessons, as well as translating and understanding verses of the Qur'an (verse interpretation) in predetermined letters. Besides that, it is added with tahfidzul qur'an as an evaluation. The results of this character education can be seen from the participation of students in habituation activities at school. Such as the habit of praying sunnah dhuha, fasting sunnah Monday-Thursday, reading the Qur'an or Asmaul Husna before learning begins, obeying teachers and school rules, and being polite to teachers and other school members.